Implementasi Dan Problematika Standar Penilaian Pendidikan Dalam Kurikulum Merdeka Sekolah/Madrasah Di Indonesia - Lina Rusliana (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
The success of education will be seen if the evaluation measuring tools used are appropriate and can measure each goal. Therefore, relevant measuring instruments are needed so that the measurement results are precise. In making the measuring instrument used, of course, must have a reference or assessment standard used. So that in this article the author is interested in looking further at the implementation and problems of educational assessment standards in the independent curriculum in Indonesia. The writing method in this article uses the literature review method (library research). Throughlibrary research carried out by the author, it is known that the Educational Assessment Standards contained in Permendikbudristek 21 of 2022,implemented in the independent curriculum and began to be implemented in the 2022/2023 school year. The scoring system in the independent curriculum does not look at how many grades (numbers) students get, but looks at how students process each lesson that is carried out, such as the ability of students to reason, find solutions to problems found around them. Various Free Learning programs have become a policy that is considered transformative in the world of education, of course there will be various changes that will be felt by teachers. This change felt by the teacher confronted him with various obstacles that needed to be addressed properly, such as the lack of experience with learning independence made it difficult for the teacher to determine the model, learning media and assessment system to be carried out, the lack of competency in mastering the material possessed by the teacher was one of the causes of difficulties. in compiling assessment instruments used in learning. The problems that occur are not an obstacle but a challenge for teachers to keep moving forward. Teachers are at the forefront of various changes in the world of education, like it or not, they have to be ready to take various efforts and have the courage to learn and try. In order not only to adapt, but also to be able to prepare students as the nation's generation to be able to answer challenges in the future. Keywords: Problems; Educational Assessment Standards; Independent curriculum.